Uterine Rupture during Pregnancy: Can Laparoscopy be Performed Safely and Effectively? - Mustafa Gazi Uçar; Abdül Hamid Güler; Tolgay Tuyan İlhan; Feyza Nur Çintesun; Çetin Çelik; Mehmet Kulhan (IMR Press, 2023)
Background: The main purpose of this study was to investigate the feasibility and safety of performing a laparoscopic intervention for the conservative management of uterine rupture (UR) during pregnancy. This study also provides a brief overview on the challenges and understanding of the management of UR in pregnancy. Methods: Patients diagnosed with UR between 2011-2021 at Selçuk University, Faculty of Medicine were evaluated, retrospectively. The reproductive history, clinical characteristics, UR symptoms and signs, predisposing factors, operative findings, complications and outcomes were assessed. The choice of treatment was determined according to the patients' age, fertility desire, the severity of disease, and hemodynamic status. A variety of options ranging from surgical rupture repair, to hysterectomy via minimally invasive surgery or laparotomy, were employed. Laparotomy was preferred in all patients with viable fetuses, and in those with hemodynamic instability. Results: A total of 23 cases of UR were operated over a 10-year period. Nine of them underwent laparoscopic surgery and the remaining 14 underwent laparotomy. The presenting signs and symptoms of UR, in order of decreasing frequency were: abdominal pain, vaginal bleeding, fetal distress/demise, non-reassuring fetal status, signs of hemodynamic changes, elevation of the fetal presenting parts and/or the absence of station changes with contractions, and the early detection of hemoperitoneum on ultrasound. The primary risk factors for UR were a history of uterine surgery, use of misoprostol during abortion and labor, obstructed labor, curettage, congenital uterine malformations and trauma. Total ruptures included 17 in the lower segment (Kerr incision) and 6 outside the lower segment. There were considerable differences in the incidence of Kerr incision site ruptures and UR in other sites. The major complication rates were higher in ruptures outside the lower segment (6/6, 100%) than lower segment ruptures (5/17, 29.4%). Hysterectomy rates in lower segment ruptures and other rupture sites were 5/17 (29.4%) and 4/6 (66.6%), respectively. Kerr incision site ruptures are easier to manage and with less catastrophic complications compared to cases of UR after trauma, and those of unscarred uteri or those with a history of uterine scars other than from a Kerr incision. Conclusions: This study provides evidence of the safety and feasibility of laparoscopic management of UR, and this may encourage surgeons to consider minimally invasive surgery in hemodynamically stable patients prior to more aggressive and radical treatments. With the appropriate skill set, laparoscopy may be considered the preferred route of intervention, even in potentially life-threatening conditions such as UR.